Studi Literatur: Pentingnya Pembelajaran Berdiferensiasi di Era Kurikulum Merdeka untuk Meningkatkan Hasil Belajar Peserta Didik - Alamia Haque Insani; Kukuh Munandar (Program Studi Pendidikan IPA FKIP Universitas Jember, 2023)
The independent curriculum implements a new paradigm of learning, one of which is independent learning. Independent learning is an approach for students to be able to choose lessons according to their interests and needs. The needs and interests of each student vary and the teacher can accommodate this diversity by implementing differentiated learning. Learning that fits the needs of students through differentiated learning can improve student learning outcomes. The purpose of this research is to review the importance of differentiated learning in the independent curriculum era to improve student learning outcomes. Based on a literature review, the results of the study show that there is an effect of differentiated learning on improving student learning outcomes. Improvement of learning outcomes as a form of implementing one or more aspects of differentiation. The differentiation aspect consists of content, process, product, and learning environment differentiation.